Opinion on influence of erythropoietin on quality of life and survival in patients with advanced non-small cell lung cancer - Zemełka, Tomasz; Rolski, Janusz; Ziobro, Marek; Michalczyk, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2007)
In the period from 01.2002 to 12.2003 in the Chemotherapy Clinic of the Oncology Centre in Krakow there was conducted a clinical investigation relating the influence of treatment with erythropoietin on advanced non-small cell lung cancer treated with derivatives of platinum. 54 patients were studied, assigned to two groups. Group A was treated with erythropoietin in the case of anaemia <10 g/dl. Group B was subjected only to observation. The percentage of remission in group A was 18.5% and in group B 25.9% (p=0.74). The time to progression in group A was 5.9 months, and group B 6.5 months and was not statistically different (p=0.17). The time of survival in group A was 12.1 months and in group B 9.4 months and was not statistically different (p=0.97). The percentages of one-year survival were comparable and were in both groups 37% ill. The average level of haemoglobin during treatments was in group A 12.4 g/dl and in group B 11.1 g/dl (p=0.81). In group A there was a statistically significant (p=0.012) higher percentage of improvements in range of complex of excessive fatigue (59.3%) than in group B (25.9%) and the time of improvement in both groups was comparable (the average 8 months). In group A 2 (7.4%) patients and in group B 6 (22%) patients three times more often the transfusions of red blood cell were executed but it was not a statistical difference (p=0.28).